2006
DOI: 10.1542/peds.2004-1587
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics Among Neonates With Hypoxic-Ischemic Encephalopathy During Whole-Body Hypothermia and Passive Rewarming

Abstract: Whole-body hypothermia resulted in reduced cardiac output, which reached normal levels at the end of passive rewarming, at normothermia. Physiologic cardiovascular mechanisms seemed to be intact to provide sufficient tissue perfusion, with normal blood lactate levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 35 publications
3
80
0
Order By: Relevance
“…In a recent study examining the cardiac hemodynamic effect of whole-body TH in newborns with HIE, using echocardiography, authors concluded that left ventricular cardiac output (LVCO) is reduced by about 67% during TH when compared to measures obtained after rewarming. This suggests that TH may limit the extent of systemic blood flow available to vital organs, including the brain (10). However, a limitation of this latter study by Gebauer et al is the absence of measures of cerebral blood flow.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a recent study examining the cardiac hemodynamic effect of whole-body TH in newborns with HIE, using echocardiography, authors concluded that left ventricular cardiac output (LVCO) is reduced by about 67% during TH when compared to measures obtained after rewarming. This suggests that TH may limit the extent of systemic blood flow available to vital organs, including the brain (10). However, a limitation of this latter study by Gebauer et al is the absence of measures of cerebral blood flow.…”
Section: Introductionmentioning
confidence: 87%
“…Newborns are generally able to maintain adequate blood pressure at low temperature achieved during TH (10,11). In a recent study examining the cardiac hemodynamic effect of whole-body TH in newborns with HIE, using echocardiography, authors concluded that left ventricular cardiac output (LVCO) is reduced by about 67% during TH when compared to measures obtained after rewarming.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al did not fi nd signifi cant differences in cardiac functions between normothermic asphyxiated newborns and asphyxiated newborns treated with hypothermia (17). In another study including seven asphyxiated patients, it was shown that cardiac output was decreased as to 67 % of normal with whole-body hypothermia and passive rewarming (18). In two recent studies, Sehgal et al had found that global cardiac functions were low in infants undergoing hypothermia (19).…”
Section: Discussionmentioning
confidence: 97%
“…Data from these preliminary clinical studies indicated that reducing body temperature by 2°C to 3°C for a prolonged period of time was possible and that the changes in blood pressure, heart rate, and cardiac output noted were of little clinical significance. [5][6][7] Large Randomized Clinical Trials of Hypothermic Neural Rescue ( Table 1) Six large randomized clinical trials of induced hypothermia for neonatal encephalopathy were published from 2005 to 2011. [8][9][10][11][12][13] Although there were some differences in the method of cooling and selection of subjects, in all trials infants were at least 35 weeks' gestation at birth; randomization was completed within 6 hours of birth; the target temperature was 33.5°C to 34.5°C; the intervention period was 72 hours, followed by slow rewarming (0.5°C/hour); and the primary outcome measure was the combined rate of death or disability, assessed at 18 to 22 months of age.…”
Section: Preliminary Studiesmentioning
confidence: 99%